2010
DOI: 10.1210/jc.2010-0527
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Phosphocreatine Recovery after Submaximal Exercise in Children and Young and Middle-Aged Adults

Abstract: Skeletal muscle PCr recovery measured by (31)phosphorous-MRS is prolonged with age, even in children and young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 24 publications
0
29
1
Order By: Relevance
“…In a previous study, Fleischman and collaborators similarly tested the association between 31 P muscle bioenergetics and maximal voluntary contraction of the knee extensor muscle (Fleischman et al ., 2010). They found that this association was no longer significant when adjusted for age and covariates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, Fleischman and collaborators similarly tested the association between 31 P muscle bioenergetics and maximal voluntary contraction of the knee extensor muscle (Fleischman et al ., 2010). They found that this association was no longer significant when adjusted for age and covariates.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in animal models and in humans have shown that skeletal muscle mitochondrial oxidative capacity declines with age (Conley et al ., 2000; Short et al ., 2005; Fleischman et al ., 2010; Peterson et al ., 2012), likely due to a decline in both total mitochondrial mass and decreased intrinsic mitochondrial functional capacity (Conley et al ., 2000). This steady decline of mitochondrial function with aging is believed to contribute to the progressive deterioration of muscle strength and quality (Metter et al ., 1999), as diminished energy production may constrain muscle performance, and dysfunctional mitochondria create oxidative stress that can damage proteins and mitochondrial DNA (Peterson et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This profile might explain the higher blood/muscle lactate and H + ion values obtained after maximal exercise in adolescents [2]. It could also be the cause of the slower recovery of some energy substrates (i.e., phosphocreatine) following exercise and the slower elimination of metabolites (i.e., lactate and H + ions) from the skeletal muscle in adolescents compared to children [23][24][25][26][27][28]. The lower oxidative profile of adolescents could therefore partly explain their slower recovery and their greater fatigability during repeated high-intensity exercise protocols.…”
Section: Energy Metabolismmentioning
confidence: 99%
“…Baseline data, but not longitudinal data, from this cohort have been published previously (10,11). Participants underwent a baseline evaluation, including a complete medical and family history; physical examination, including Tanner staging by a pediatric endocrinologist (A.F.…”
Section: Methodsmentioning
confidence: 99%